Hippocampal Viral-Mediated Urokinase Plasminogen Activator (uPA) Overexpression Mitigates Stress-Induced Anxiety and Depression in Rats by Increasing Brain-Derived Neurotrophic Factor (BDNF) Levels - Amine Bahi; Jean-Luc Dreyer (Biomolecules)
Emerging evidence suggests the serine protease, urokinase plasminogen activator (uPA), may play an important role in the modulation of mood and cognitive functions. Also, preliminary evidence indicates that uPA modulates BDNF activity that is known to be involved in the pathogenesis of mood disorders. However, the physiological functions of uPA in specific brain regions for mediating stress-related emotional behaviors remain to be elucidated. Therefore, the aim of this study was to assess the role of ectopic uPA expression on anxiety- and depression-like behaviors following social defeat stress in rats. For this purpose, we inspected the behavioral outcomes following bilateral stereotaxic delivery of uPA-overexpressing lentiviral vectors in the hippocampus using a series of behavioral tests. Results show that hippocampal uPA gain-of-function prevented stress-elicited anxiogenic-like effects, as determined in the marble burying, open field, and elevated plus maze tests, with no alterations in spontaneous locomotor activity. Also, ectopic uPA overexpression resulted in anti-depressant-like effects in the sucrose splash, tail suspension, and forced swim tests. Most importantly, uPA overexpression increased hippocampal BDNF levels, and a strong positive correlation was found using the Pearson test. Moreover, the same correlation analysis revealed a strong negative relationship between uPA mRNA and parameters of anxiety- and depression-like behaviors. Taken together, this work highlights the importance of considering uPA activation and provides new insights into the mechanisms involved in the pathophysiology of stress-elicited mood illnesses, which should help in the development of new approaches to tackle depression and anxiety disorders.